Workers as creditors: Performance bonds and efficiency wages - Ritter, Joseph A.; Taylor, Lowell J. (American Economic Review, 1994)
From the standpoint of economic theory, the difficulty in regulating workers' performance distinguishes labor markets from commodity markets. Commodities do not respond to incentives. Workers, in contrast, can quit, steal, be hung over, refuse to cooperate with other workers, or generally work at low effort levels. Since direct monitoring is often costly and unreliable, it may not be the profit-maximizing solution to this problem. Economists have discussed various schemes to make productive behavior incentive-compatible for workers. The most frequently discussed schemes fall into two broad categories: efficiency wages and deferred compensation or bonding schemes.! These schemes have been suggested as explanations for a wide variety of labormarket features that appear anomalous from the conventional supply-and-demand perspective. Efficiency-wage models can generate equilibria in which there is involuntary unemployment and in which identical workers are paid different wages in jobs that are otherwise equally attractive. George A. Akerlof and Janet L. Yellen (1985) have argued that they can provide an important component of a model of business cycles. Deferred-compensation schemes have been proposed as explanations for upward-sloping age-earnings profiles, mandatory retirement, pensions, and hierarchical (tournament) promotion structures.2 Because bonding is costless to firms, efficiency-wage and bonding strategies are often viewed as mutually incompatible; profit-maximizing firms should offer efficiency wages only in situations where bonding is impossible. One widely held view argues that in labor markets where agency issues arise, these problems are effectively solved by various bonding arrangements (and moreover, that this observation helps to explain otherwise peculiar features of some labor markets, as mentioned above). It follows that efficiency wages do not generally exist. Proponents of efficiency-wage theory argue that there is considerable evidence of widespread agency problems (e.g., large expenditures by many firms on monitoring) and that there are barriers to the use of bonds, notably moral hazard on the part of firms or legal constraints. Efficiency wages cannot therefore be ruled out a priori as an equilibrium solution to these agency problems.3 In this paper we study these issues surrounding efficient worker compensation in a framework that allows heterogeneity among firms and integrates the financial and